Prática de enfermeiros da equipe da Estratégia Saúde da Família em comunidades quilombolas sob o prisma da Ética Feminista - Lilian Cristina Rezende (2020)
In Brazil, the role of nurses in the Family Health Strategy has been of fundamental importance for the expansion and consolidation of the health care model. Recognizing the cultural diversity that exists in the country, including in this scenario the quilombola population, the practice of nurses requires the coverage of normative, theoretical, political, ethical and moral knowledge. Thus, reflections on moral values are presented in the complexity of the nurse's work, which refers to the practice of shared responsibility among the subjects in a limited context. Thus, nurses must consider the values of those to whom they provide care and the construction of morality in quilombola communities. It is assumed that the nurse conducts his practice considering the cultural and socio-historical diversity of the population since the ways of living incorporate different senses and meanings of health. The objective of the study was to understand the practice of nurses from the Family Health Strategy team in quilombola communities, under the prism of feminist ethics. This is a single, integrated, qualitative case study. Data collection was carried out from February to June 2018 through individual interviews, group interviews and observation. The scenario was the Family Health Strategy in five municipalities in the Metropolitan Region of Belo Horizonte-MG. Participants were all (seven) nurses and 59 quilombolas. The data were analyzed in the light of Content Analysis with the aid of the Atlas.ti 8.0 software. The results indicated that the practice will be effective when built on relationships, within the social context, through (re) knowledge of social and cultural issues, as well as the individual/family/community life forms. The study showed the characteristics of quilombos and the relationship of kinship, which involve cultural (music, dance) and religious expressions/manifestations of ancestors, associated with slavery and Afro-descent. In addition, there were difficulties regarding the implementation of the practice, such as the distance from the community to the health unit for rural communities; absence of a community health agent close to the communities; work overload, a large volume of population attached. The relevance of the theme in terms of discussing the practice in quilombola communities in the context of the FHS is emphasized. This work allows a reflection on the particularities of social groups, as well as the training of professionals to work in the Family Health Strategy, especially with regard to the development of cultural, moral and political competence and the adoption of a critical and responsible posture to develop their activities with minority groups.